1984
DOI: 10.1021/bi00300a011
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry and specificity of lipid-protein interaction with myelin proteolipid protein studied by spin-label electron spin resonance

Abstract: The interaction of spin-labeled lipids with the myelin proteolipid apoprotein in complexes with dimyristoylphosphatidylcholine of varying lipid/protein ratios has been studied with electron spin resonance spectroscopy. A first shell of approximately 10 lipids per 25 000-dalton protein is found to be motionally restricted by the protein interface. This stoichiometry is consistent with a hexameric arrangement of the protein in the membrane. A selectivity of the various spin-labeled lipids for the motionally rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
65
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 21 publications
20
65
1
Order By: Relevance
“…It is found that the protein has very little effect on either the degree of order of the lipid chain or the population of gauche rotational isomers but increases the rotational correlation times for chain fluctuation, chain rotation, and trans-gauche isomerism by a factor of 10 or more. These results are fully consistent with those obtained from ESR spectroscopy of spin-labeled lipids (6,7). …”
supporting
confidence: 91%
“…It is found that the protein has very little effect on either the degree of order of the lipid chain or the population of gauche rotational isomers but increases the rotational correlation times for chain fluctuation, chain rotation, and trans-gauche isomerism by a factor of 10 or more. These results are fully consistent with those obtained from ESR spectroscopy of spin-labeled lipids (6,7). …”
supporting
confidence: 91%
“…This oligomerisation of the proteolipid proteins has been reported previously; using electron spin resonance, Brophy et al (1984) suggested a possible hexameric complex to account for the smaller than expected number of lipids associated with the protein. Using ultracentifugation, Smith et al (1984) also suggested a hexameric complex, whereas Lavaille et al (1979) showed that PLP is not monomeric in 2-chloroethanol.…”
Section: Introductionsupporting
confidence: 82%
“…In addition, our figures are also similar to those proposed by Curatolo et al [lo], who estimated in 30 lipids the number of Myr2GroPCho molecules that could be accommodated around the PLA molecule, the latter idealised as a circular cylinder not protruding into the aqueous phase. However Brophy et al [7], on the basis of ESR spectroscopy, have…”
Section: Fluorescence Studiesmentioning
confidence: 99%